Analisa Tingkat Korosi Atmosferik Pada Baja Struktural Dikawasan Aceh Barat dan Nagan Raya - Joli Supardi (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2015)
The west coast of Aceh region is an area that is passed directly to the Indian Ocean, the Malacca Strait and the Gulf of Bengal. The tsunami that Aceh in December 2004 has led to the greater part of the coastal region of Aceh, including the region of Aceh Barat and Nagan Raya merged in seawater and the impact on the destruction of the environment around the coast. This condition causes the infrastructure in tsunami affected area becomes more susceptible to corrosion attack. This condition is exacerbated by the fact that the Aceh region is an area that is prone to earthquakes that have corroded infrastructure can suddenly collapsed during the earthquake occurred at a smaller scale. This study aims to look at the effect on the rate of corrosion of structural steel in the region of Aceh Barat and Nagan Raya. This research is done on location Peunaga Pasi For West Aceh region and village Kubang Gajah To Nagan Raya area. Testing methods to lose weight with the exposure time period of five months. The results showed that the corrosion rate of the highest value for western Aceh region ranged from 0.74 to 4.29 mpy and to Nagan Raya ranged from 0.85 to 2.61 mpy. For all types of steel in this region the level of corrosion rate is still relatively low. Keyword : Atmospheric Corrosion, Steel Construction, Corrosion rate.